Evidence for the decay X(3872) → J/ψω - Amo Sanchez, Pablo del; Adametz, Aleksandra; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We present a study of the decays B0,+→J/ψπ+π−π0K0,+, using 467×106 B¯¯¯B pairs recorded with the BABAR detector. We present evidence for the decay mode X(3872)→J/ψω, with product branching fractions B(B+→X(3872)K+)×B(X(3872)→J/ψω)=[0.6±0.2(stat)±0.1(syst)]×10−5, and B(B0→X(3872)K0)×B(X(3872)→J/ψω)=[0.6±0.3(stat)±0.1(syst)]×10−5. A detailed study of the π+π−π0 mass distribution from X(3872) decay favors a negative-parity assignment.
Gesehen am 14.05.2024
BABAR Collaboration: P. del Amo Sanchez, A. Adametz, J. Marks, S. Schenk, U. Uwer, [und 440 weitere]